2016
DOI: 10.1002/nop2.58
|View full text |Cite
|
Sign up to set email alerts
|

Preceptor characteristics and the socialization outcomes of new graduate nurses during a preceptorship programme

Abstract: AimThe purpose of this study was to explore the relationships between preceptor characteristics (emotional intelligence, personality and cognitive intelligence) and new graduate nurse socialization outcomes regarding turnover intent, job satisfaction, role conflict and ambiguity during a preceptorship programme. To date, no studies have explored these relationships.DesignA cross‐sectional and multi‐site design with purposeful sampling.MethodsDyads of preceptors and new nurses were recruited at the end of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…In the current research, each preceptor had developed their own expectations and associated methods of support. A correlation was found between the present study and the Canadian study conducted by Lalonde and McGillis Hall (2017), whereby preceptor traits were related to graduate nurse outcome. In their study of 41 preceptors and 44 graduate nurses, the preceptor who demonstrates openness, conscientiousness and a calm emotional stance all connected to negative graduate outcomes such as role ambiguity, job dissatisfaction and turnover intent.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In the current research, each preceptor had developed their own expectations and associated methods of support. A correlation was found between the present study and the Canadian study conducted by Lalonde and McGillis Hall (2017), whereby preceptor traits were related to graduate nurse outcome. In their study of 41 preceptors and 44 graduate nurses, the preceptor who demonstrates openness, conscientiousness and a calm emotional stance all connected to negative graduate outcomes such as role ambiguity, job dissatisfaction and turnover intent.…”
Section: Discussionsupporting
confidence: 69%
“…In their study of 41 preceptors and 44 graduate nurses, the preceptor who demonstrates openness, conscientiousness and a calm emotional stance all connected to negative graduate outcomes such as role ambiguity, job dissatisfaction and turnover intent. Particularly, it was suggested that conscientious preceptors may have higher expectations regarding graduate nurse performance (Lalonde & McGillis Hall, 2017). The preceptors within the current study described similar traits such as openness and transparency in providing support.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the preceptorepreceptee pairs, anger can have detrimental effects on the educatorelearner relationship, the teaching and learning process, and satisfaction with the preceptorship program, and these preceptorship experiences may be followed by lack of job satisfaction and burnout of both preceptors and NGNs [5,9,10,23]. Furthermore, anger can be expressed toward the counterpart, directly or indirectly, in the form of verbal abuse and ignoring, and anger felt by preceptors and NGNs would mutually lead to burnout and job satisfaction [10,11,17,24]. Therefore, it is necessary to focus on anger and its interactive impact on job satisfaction and burnout in the context of nursing preceptorship.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mentoring is also capable of improving job satisfaction, improving the ability to communicate with both patients and with other health workers, and lower stress levels of nurses (Bontrager, Hart, & Mareno, 2016;Lalonde & Mcgillis Hall, 2016). Mentoring is usually used in situations where a nurse with more ability and experience provides support to nurses, who have lower ability and experience that are conducted formally or informally.…”
Section: Introductionmentioning
confidence: 99%